2017
DOI: 10.4038/rjs.v8i1.22
|View full text |Cite
|
Sign up to set email alerts
|

Farm waste utilization among farmers in Irepodun local government area, Kwara state, Nigeria: implication for extension education service delivery

Abstract: Abstract. The study examined the utilization of farm waste among farmers in Irepodun Local Government Area of Kwara State, Nigeria. Structured interview schedule was used to elicit data from 120 farmers in the study area. Results revealed that more than half (58.4%) of the respondents were crop farmers who grow majorly maize and cassava on a subsistence scale. The major farm wastes generated in the area were maize cobs, husk and stalk (62.5%) and cassava stalk and peels (60%). Majority of the farmers got rid o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The utilization of residues appears variable in Nigeria depending on residue types and farmer practices. A survey conducted with farmers in the Irepodun Local Government Area showed that 53.7% of respondents did not utilize farm wastes, including maize cobs, husks and stalk, soybean straw and pods, and cassava stalk and leaves [70]. A separate survey reported a utilization of ~40% for cereals and ~94% for legumes [65].…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of residues appears variable in Nigeria depending on residue types and farmer practices. A survey conducted with farmers in the Irepodun Local Government Area showed that 53.7% of respondents did not utilize farm wastes, including maize cobs, husks and stalk, soybean straw and pods, and cassava stalk and leaves [70]. A separate survey reported a utilization of ~40% for cereals and ~94% for legumes [65].…”
Section: Discussionmentioning
confidence: 99%
“…This practice contributes to contamination of the environment as well as foods with pathogenic and antimicrobial resistant bacteria. Oladipo et al ( 25 ) in their study in Kwara State Nigeria noted that farmers deposited farm waste in nearby streams and rivers. This may have serious impact on health and general well-being of both humans and animals with its attendant serious economic implications.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise in Irepodun Local Government Area of Kwara State, Nigeria. The major farm wastes generated in the area include maize cobs, husk and stalk (62.5%) and cassava stalk and peels (60%) and majority of the farmers got rid of their farm waste through burning while others do not utilize the waste they generate from their farms [19]. Another concern with burning of these waste is that diseases such as, respiratory disorders, lungs and heart diseases and cancers could be triggered by inhaling toxic fumes from open fires, in a recently published report titled, "Toxic blaze: the true cost of crop burning", by the United Nations Environment Programme (UNEP) stated that carbon produced through open burning is 460 -1,500 times higher in its tendency to escalate global warming than the widely known carbon dioxide [9,20].…”
Section: Introductionmentioning
confidence: 99%